Trust in the Government as a Result of its Social Policy (Based on the Results of Sociological Research in the Republic of Angola) - L. D. Kozyreva; A. A. Santos (Управленческое консультирование, 2021)
The article presents the results of an empirical study of the “vertical” form (P. Shtompka) of trust in the authorities on the part of the population of the Republic of Angola, conducted at the end of 2020. The research methodology (classical and modern studies of the phenomenon of trust), methods of collecting primary information (included observation, a survey in the form of a standardized interview) are described. The factors influencing the attitude of citizens to the government and causing distrust of its social policy are analyzed. The attitude to the key institutions of civil society on the scale of “trust-distrust” is shown. Based on the results of the study, a forecast is made about the strengthening of distrust of power structures and the growth of tension in the country.